The Diversity and Conservation Status of Snakes in Rawa Mekar Jaya, Riau, Indonesia - Adjie, Agung Purnomo; Setyawatiningsih, Sri Catur (UIN Sunan Gunung Djati Bandung, 2021)
Snakes in Mekar Jaya mangrove ecosystem have the potential be ecotourism objects. On the other hand ecotourism activities might reduce the quality of wildlife habitat, including that of the snake. This study aimed to determine the diversity and status of snake species in the mangrove ecosystem of Rawa Mekar Jaya. A transect of 20 x 50 m was made in three stations: rivers (S1), ecotourism route (S2), and dense mangroves (S3). The observation was carried out at low tide and repeated three times with a span of 2 days. Snake data was collected using the Visual Encounter Survey (VES) method. We revealed 59 snakes in the mangrove area of Rawa Mekar Jaya consisting of 3 species namely Boiga dendrophila, Cerberus rynchops, and Trimeresurus purpureomaculatus. B. dendrophila and C. rhyncops are mangrove specialists. The Shannon Wiener diversity index value (H ') for all observation stations is below one, so it is classified as low. All types of snakes found are not protected and classified as the least concern. C. rynchops is included in the CITES appendix III